2022
DOI: 10.3389/fneur.2021.758580
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Prediction of Freezing of Gait in Parkinson's Disease: A Prospective Cohort Study

Abstract: Objective: Freezing of gait (FOG) is a disabling complication in Parkinson's disease (PD). Yet, studies on a validated model for the onset of FOG based on longitudinal observation are absent. This study aims to develop a risk prediction model to predict the probability of future onset of FOG from a multicenter cohort of Chinese patients with PD.Methods: A total of 350 patients with PD without FOG were prospectively monitored for ~2 years. Demographic and clinical data were investigated. The multivariable logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…FOG is generally partially responsive to dopaminergic medication, and episodes are therefore more frequent and of longer duration when dopaminergic medication has worn off. Paradoxically, it has been found that higher daily doses of levodopa at baseline in a cohort study has been shown to predict worse FOG over time 26…”
Section: Discussionmentioning
confidence: 99%
“…FOG is generally partially responsive to dopaminergic medication, and episodes are therefore more frequent and of longer duration when dopaminergic medication has worn off. Paradoxically, it has been found that higher daily doses of levodopa at baseline in a cohort study has been shown to predict worse FOG over time 26…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports of multivariable modeling also reflect a significantly diverse set of 40 features predicting FOGConv (Supplementary Table 3). Of these, 4 studies reported disease duration [49,51,57,62] and depression scores [48,49,52,62]; 3 datasets in 5 studies reported some variation of greater postural instability gait disorder (PIGD) scores [49,55,56,59,60]; and 2 studies reported age [49,60], LEDD [47,62] and gait speed [48,52] as predictors of FOG conversion. Two studies, both using the PPMI dataset, also reported lower CSF A␤ 42 levels [55,59] while one group reported decreased dopamine transporter tracer binding in two publications [55,56] as significant predictors of FOG conversion.…”
Section: Discussionmentioning
confidence: 99%
“…However, FOG has been reported in a percentage of patients even prior to initiation of levodopa therapy [56]. Phenotypic conversion to FOG has been associated with earlier levodopa use [61] and higher daily levodopa dose on univariate [49,50,57,61] and multivariable [47,62] analyses. In our study, duration of levodopa use and LEDD also both had AUC values of 0.775 and 0.815 respectively for classifying the noFOG and FOGConv groups (Supplementary Table 5), however these AUC values were lower than those for progression rates of gait parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations